Defining households that are underserved in digital payment services - Claire Greene; Fumiko Hayashi; Alicia Lloro; Oz Shy; Joanna Stavins; Ying Lei Toh (Federal Reserve Bank of Boston, 2024)
US households that lack digital means of making and receiving payments cannot participate fully in an increasingly digitized economy. Assessing the scope of this problem and addressing it requires a definition of households that are underserved in digital payments. Traditional definitions of households underserved in the banking system-those that are unbanked and those that are underbanked-do not account for the ownership of nonbank transaction accounts that can be used to make and receive digital payments. In this paper, we define households underserved in digital payments by considering four key elements-access, use, safety, and affordability-and discuss how researchers may assess these elements to quantify the share of households underserved in digital payments.
Keywords: D12; D18; G21; G23; 330; Digital payments inclusion; underserved; fintech; nonbanks